An Efficient Retinex Image Enhancement based on 2D DTCWT - Mahalakshmi, Badiginchala; Mahaboob, Shaik. Taj (International Journal of Computer Sciences and Engineering, 2025)
The task of image enhancement is focused on restoring and clarifying the corrupted images to improve their quality, and image enhancement methods has been widely applied to numerous image analysis techniques including pattern recognition, image fusion, image segmentation and so forth. Among the various methods used to enhance the image, algorithms created from retinex theory have received more and more attention and have been commonly used in many applications. This paper describes a retinex theory based method for contrast and illuminance enhancement in images of low light or unevenly illuminated scenes. This method firstly transformsimage from RGB color space to HSV colorspace, and decomposes the value channel using dual-tree complex wavelet transform. Then, to process the lesser frequency component of the image, an improved adaptive local tone mapping method is utilized and wavelet shrinkage method and fuzzy enhancement method are applied to denoise and enhance the reconstructed and a statistical histogram optimization method is used. After that, the enhanced value channel is the image is transformed back to RGB color space. Findings from experiments support the method suggested by this paper which performs very well with enhancement and de-noise of the corrupted images.